PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR BASIC MATERIALS DAN ENERGY Di ASEAN TAHUN 2022-2024 - Firda Iffatus Suroyya; Mariana Mariana (ISTISMAR, 2026)
This study aims to examine the impact of Enviromental, Social, and Governance (ESG) factors on financial performance, with Debt to Asset ratio (DAR) serving as a moderating variable. The research employs a quantitative approach using EViews 13 software, and data anaysis is conducted via panel data regression. The study utilitizes a sample of parent companies operating in the Basic Materials and Energy sectors in ASEAN from 2022 to 2024. The results of the study indicate that the Environmental variable has a significant negative effect on financial performance, as proxied by return on Assets (ROA). Meanwhile, the Social and Governance variables do not have a significant effect on the company's financial performance. Simultaneously, ESG variables have a significant effect on a company's financial performance. Additionally, the debt-to-asset ratio (DAR), as a control variable, has a positive and significant effect on the company's financial performance. Keywords: Environmental, Social, Governance, Financial Performance, Debt to Asset ratio (DAR)